Male Neighbors’ Behavior: Bystander Effect in Domestic Violence Cases - Nido Dipo Wardana; Margaretha Margaretha (Journal of Educational, Health and Community Psychology, 2018)
This research was twofold and aimed to explore male neighbors’ behavior as bystanders of domestic violence (DV) cases. Study 1 used survey on 94 male respondents to obtain description about bystander behavior and examine the relationship between situational barriers, neighborhood cohesion, and bystander’s intention to help victims. Study 2 used qualitative approach with instrumental case study, involving three male participants to understand the dynamic of bystander effect on male neighbors who had witnessed DV. Bystander effect (BS) is a phenomenon in which individual is less likely to intervene in an emergency if bystander present. BS was analyzed based on three root psychological processes, namely: diffusion of responsibility, audience inhibition, and pluralistic ignorance; the three appeared in the bystander intervention stages. An important finding was the role of neighborhood cohesion which interacted with DV-supporting norm; such that bystanders from highly cohesive neighborhood were resistant to help victims of real DV cases although social cohesion was a notable predictor of intention to help. The evidences in this research expanded Latané’s (1981) theory of social impact as well as supporting Levine (1999) and Banyard and colleagues’ (2004) notion of distorted thinking as a root of bystander inaction. Implication of the findings for community-based interventions is discussed.